Numerical Investigation of the Effect of the Number of Blades and the Twist Ratio of the Twisted tape on the Performance of the Double-Pipe Heat Exchanger - Mohammad Reza Tavakoli; Saeed Mohebi (مجله مدل سازی در مهندسی)
In this paper, the effect of a fixed twisted-tape placed in the inner tube of a double-pipe heat exchanger is investigated using numerical simulation. A twisted-tape with three and four blades with different twist ratios is placed in the inner tube of the heat exchanger, and the Nusselt number, friction coefficient, and overall performance coefficient of the heat exchanger are studied. The flow velocity in the outer tube is considered constant, but the Reynolds number of the flow at the inlet of the inner tube is changed in the range of 5000 to 12000. The results showed that in all cases, placing a twisted-tape inside increases the Nusselt number and friction coefficient. The highest increase of these two parameters is 244 and 490 percent, respectively. By increasing the Reynolds number, the friction coefficient and the overall performance coefficient decreased, while the Nusselt number increased. This increase reaches about 80% in the case that has a twisted-tape with a twist ratio of 4. Also, reducing the twist ratio increases the turbulence of the flow and thus increases the Nusselt number, pressure drop, friction coefficient, and the overall performance coefficient. The maximum increase in the friction coefficient due to the reduction of the twist ratio from 8 to 4 was equal to 43%, occurred in the Reynolds number of 5000 and the three-bladed twisted-tape. Increasing the number of blades of the twisted tape has a direct effect on the pressure drop and friction coefficient and causes a decrease in the overall performance coefficient.